Phytoplankton Diversity as a Bioindicator for Coastal Water Quality of Kecinan Beach North Lombok Regency - Shofiana, Dwi Auliya; Candri, Dining Aidil; Japa, Lalu; Setyaningrum, Tri Wahyu; Munawaroh, Anggi Nurhardiyanti (Jurnal Pijar Mipa, 2025)
Kecinan Beach is one of the beaches on Lombok Island with many tourism activities. The activities in Kecinan Beach can influence the water quality, as the waters may receive waste from surrounding areas, leading to potential pollution or a decline in water quality. Phytoplankton are living organisms that can indicate whether a water body is polluted, which can be marked by changes in the community structure of phytoplankton, particularly in abundance and diversity. Water quality based on phytoplankton diversity as a bioindicator in Kecinan Beach has not been reported. This study was conducted to analyze the water quality of Kecinan Beach based on phytoplankton diversity as a bioindicator. Samplings were carried out in 9 sites in 3 stations during the month of March to June 2024. Samples were collected using a plankton net of 20µm mesh size. Samples were preserved in 4% formalin preservation and laboratory observation was conducted in the biology laboratory of FMIPA University of Mataram. The study identified 56 species from  3 classes, 21 families and 30 phytoplankton genera. The phytoplankton abundance in the coastal waters of Kecinan Beach was 126.667 ind/L. The species dominance index of phytoplankton of coastal waters of Kecinan Beach was 0.258, indicating no species dominance to each other. Rhabdonema arcuatum was identified as the highest (158%) species importance value. The species diversity index of phytoplankton of the coastal waters of Kecinan Beach was a moderate category. Based on the species diversity index, it can be said that the waters of Kecinan Beach are not polluted.